Informal settlement upgrading and the effect of governmentality on women's social networks : a case study of New Rest and Makhaza, Cape Town - Massey, Ruth Thokozile (Stellenbosch : Stellenbosch University, 2013)
Thesis (PhD)--Stellenbosch University, 2013.